Is the Best Fitting Curve Always Unique? - N. Chernov; Q. Huang; H. Ma (Journal of Mathematics)
Fitting straight lines and simple curved objects (circles, ellipses, etc.) to observed data points is a basic task in computer vision and modern statistics (errors-in-variables regression). We have investigated the problem of existence of the best fit in our previous paper (see Chernov et al. (2012)). Here we deal with the issue of uniqueness of the best fit.